Revisiting The Interpretation of The Indonesian Criminal Procedure Code: Legal Basis for Witnessteleconferencing - Oktaviandra, Surya (Jurnal Hukum dan Peradilan, 2025)
Remote witness examination through teleconference media has been used for several criminal cases in Indonesia. However, it was assumed that its legal standing based on Criminal Procedure Code (KUHAP) remains unclear and insufficient. Therefore, many legal scholars and practitioners look beyond the existing laws. This paper argues that the existing law can support the legal basis and implementation of witness teleconferencing in criminal cases without necessarily requiring new legislation. This normative juridical study collects and analyzes legal materials data from several laws and jurisprudences in Indonesia relating witness examination. The result shows that criminal witness examination through teleconference media is valid and enforceable under KUHAP by employing broad interpretation of Article 160 KUHAP. Nevertheless, for greater result on seeking the material truth, it is necessary to regulate the application of witness teleconferencing to ensure witness statements can be delivered smoothly and independently. This finding revitalizes the legal basis concept for remote examination in criminal proceedings. It may facilitate consideration by authorities and legislators in developing laws related to the Criminal Procedure Code.